tan⁻¹ 1/2 + tan⁻¹ 1/5 + tan⁻¹ 1/8=π/4,Prove it.
Answers
Answered by
2
LHS = tan^-1(1/2) + tan^-1(1/5) + tan^-1(1/8)
= [tan^-1(1/2) + tan^-1(1/8) ] + tan^-1(1/5)
we know, tan^-1x + tan^-1y = tan^-1{(x + y)/(1 - xy)}
so, tan^-1(1/2) + tan^-1(1/8) = tan^-1{1/2 + 1/8}/{1 - /1/2 × 1/8}
=tan^-1 {(4 + 1)/8}/{(16 - 1)/16}
= tan^-1{10/15}
= tan^-1{2/3}
now, tan^-1{1/2} + tan^-1{1/8} = tan^-1{2/3}
so, [tan^-1(1/2) + tan^-1(1/8) ] + tan^-1(1/5) = tan^-1{2/3} + tan^-1{1/5}
= tan^-1{(2/3 + 1/5)}/{1 - 2/3 × 1/5}
= tan^-1{(10 + 3)/15}/{(15 -2)/15}
= tan^-1{13/13}
= tan^-1{1} = π/4 = RHS
= [tan^-1(1/2) + tan^-1(1/8) ] + tan^-1(1/5)
we know, tan^-1x + tan^-1y = tan^-1{(x + y)/(1 - xy)}
so, tan^-1(1/2) + tan^-1(1/8) = tan^-1{1/2 + 1/8}/{1 - /1/2 × 1/8}
=tan^-1 {(4 + 1)/8}/{(16 - 1)/16}
= tan^-1{10/15}
= tan^-1{2/3}
now, tan^-1{1/2} + tan^-1{1/8} = tan^-1{2/3}
so, [tan^-1(1/2) + tan^-1(1/8) ] + tan^-1(1/5) = tan^-1{2/3} + tan^-1{1/5}
= tan^-1{(2/3 + 1/5)}/{1 - 2/3 × 1/5}
= tan^-1{(10 + 3)/15}/{(15 -2)/15}
= tan^-1{13/13}
= tan^-1{1} = π/4 = RHS
Answered by
2
Hello,
Solution:
we know that
![{tan}^{ - 1} x + {tan}^{ - 1} y = {tan}^{ - 1} ( \frac{x + y}{1 - xy} ) \\ \\ {tan}^{ - 1} \frac{1}{2} + {tan}^{ - 1} \frac{1}{5} = {tan}^{ - 1} ( \frac{ \frac{1}{2} + \frac{1}{5} }{1 - \frac{1}{10} } ) \\ \\ = {tan}^{ - 1} ( \frac{7}{9} ) \\ \\ {tan}^{ - 1} \frac{7}{9} + {tan}^{ - 1} \frac{1}{8} = {tan}^{ - 1} ( \frac{ \frac{7}{9} + \frac{1}{8} }{1 - \frac{7}{72} } ) \\ \\ = {tan}^{ - 1} ( \frac{ \frac{56 + 9}{72} }{ \frac{72 - 7}{72} } ) \\ \\ = {tan}^{ - 1} ( \frac{65 \times 72}{65 \times 72} ) \\ \\ = {tan}^{ - 1} (1) \\ \\ = \frac{\pi}{4} \\ \\ since \: \: \tan( \frac{\pi}{4} ) = 1 {tan}^{ - 1} x + {tan}^{ - 1} y = {tan}^{ - 1} ( \frac{x + y}{1 - xy} ) \\ \\ {tan}^{ - 1} \frac{1}{2} + {tan}^{ - 1} \frac{1}{5} = {tan}^{ - 1} ( \frac{ \frac{1}{2} + \frac{1}{5} }{1 - \frac{1}{10} } ) \\ \\ = {tan}^{ - 1} ( \frac{7}{9} ) \\ \\ {tan}^{ - 1} \frac{7}{9} + {tan}^{ - 1} \frac{1}{8} = {tan}^{ - 1} ( \frac{ \frac{7}{9} + \frac{1}{8} }{1 - \frac{7}{72} } ) \\ \\ = {tan}^{ - 1} ( \frac{ \frac{56 + 9}{72} }{ \frac{72 - 7}{72} } ) \\ \\ = {tan}^{ - 1} ( \frac{65 \times 72}{65 \times 72} ) \\ \\ = {tan}^{ - 1} (1) \\ \\ = \frac{\pi}{4} \\ \\ since \: \: \tan( \frac{\pi}{4} ) = 1](https://tex.z-dn.net/?f=+%7Btan%7D%5E%7B+-+1%7D+x+%2B++%7Btan%7D%5E%7B+-+1%7D+y+%3D++%7Btan%7D%5E%7B+-+1%7D+%28+%5Cfrac%7Bx+%2B+y%7D%7B1+-+xy%7D+%29+%5C%5C++%5C%5C++%7Btan%7D%5E%7B+-+1%7D++%5Cfrac%7B1%7D%7B2%7D+%2B++%7Btan%7D%5E%7B+-+1%7D++%5Cfrac%7B1%7D%7B5%7D++%3D++%7Btan%7D%5E%7B+-+1%7D+%28+%5Cfrac%7B+%5Cfrac%7B1%7D%7B2%7D++%2B++%5Cfrac%7B1%7D%7B5%7D+%7D%7B1+-++%5Cfrac%7B1%7D%7B10%7D+%7D+%29+%5C%5C++%5C%5C++%3D++%7Btan%7D%5E%7B+-+1%7D+%28+%5Cfrac%7B7%7D%7B9%7D+%29+%5C%5C++%5C%5C++%7Btan%7D%5E%7B+-+1%7D++%5Cfrac%7B7%7D%7B9%7D+%2B++%7Btan%7D%5E%7B+-+1%7D++%5Cfrac%7B1%7D%7B8%7D++%3D++%7Btan%7D%5E%7B+-+1%7D+%28+%5Cfrac%7B+%5Cfrac%7B7%7D%7B9%7D++%2B++%5Cfrac%7B1%7D%7B8%7D+%7D%7B1+-++%5Cfrac%7B7%7D%7B72%7D+%7D+%29+%5C%5C++%5C%5C++%3D++%7Btan%7D%5E%7B+-+1%7D+%28+%5Cfrac%7B+%5Cfrac%7B56+%2B+9%7D%7B72%7D+%7D%7B+%5Cfrac%7B72+-+7%7D%7B72%7D+%7D+%29+%5C%5C++%5C%5C++%3D++%7Btan%7D%5E%7B+-+1%7D+%28+%5Cfrac%7B65+%5Ctimes+72%7D%7B65+%5Ctimes+72%7D+%29+%5C%5C++%5C%5C++%3D++%7Btan%7D%5E%7B+-+1%7D+%281%29+%5C%5C++%5C%5C++%3D++%5Cfrac%7B%5Cpi%7D%7B4%7D++%5C%5C++%5C%5C+since+%5C%3A++%5C%3A++++%5Ctan%28+%5Cfrac%7B%5Cpi%7D%7B4%7D+%29+%3D+1)
hence proved that tan⁻¹ 1/2 + tan⁻¹ 1/5 + tan⁻¹ 1/8=π/4
Hope it helps you
Solution:
we know that
hence proved that tan⁻¹ 1/2 + tan⁻¹ 1/5 + tan⁻¹ 1/8=π/4
Hope it helps you
Similar questions